Avanços da degradação ambiental na região Nordeste do Brasil - Gurjão, Natália de Oliveira (2020)
The Brazilian Northeast is the poorest region in the country, and its population, which depends heavily on agricultural production, suffers from the adversities associated with aggressive and unstable climatic conditions, land structure , technological backwardness, and the degradation of its natural resources - caused , largely, due to the anthropic action of predatory agricultural practices and inadequate cleaning procedures for cultivation areas - lack or deficient technical assistance, overgrazing, among other causes. The present work aims to map the degree of environmental degradation of the municipalities that make up the nine states of Northeast Brazil, through the creation of the Environmental Degradation Index (IDA). For the formation of IDA, indicators that cover ecological, economic and social variables are used. The indicators were transformed into partial indices in order to standardize the values, making them dimensionless. The weights assigned to each partial index used in the construction of the IDA were obtained using Linear Programming techniques. The data used in the research are collected from the last three Agricultural Censuses: 1995/1996, 2006 and 2017 and the GDP per capita of the years 1999, 2006 and 2017, extracted from the Brazilian Institute of Geography and Statistics (IBGE). The generated IDA is measured as a percentage and is contained in the range between zero and one hundred. The closer to 100% the estimated value for IDA, the more degraded the municipality is. In contrast, the lower the percentage of IDA, the less degraded the municipality is in relation to the weighting of the four partial indixes. Therefore, it seeks to assess the current stage of all municipalities in the Northeast, in each year of the survey, and also to carry out the dynamic assessment of the evolution of environmental degradation indicators and IDA. The dynamic assessment was carried out using statistical tests and estimation of discrete geometric growth rates (TGC) to measure the evolution, stagnation or involution of degradation in the municipalities between the years of study. The survey also constructed IDA assessment metrics for each year, in addition to subdividing it into levels of degradation: Low, Medium, High and Very High based on the limits established by the expected value and standard deviation. Tests were carried out based on the regression analysis, in order to verify if there are differences between the degradation levels of the municipalities that make up the semi-arid region of the Northeast, vis-à-vis those that are not part of this ecosystem. The results show an overview of static degradation for the years 1995/96, 2006 and 2017, as well as the dynamic evolution between these three years for all municipalities in the Northeast. Finally, it was found that environmental degradation, in general, increased in the Northeast region in all states, however, in some of them it first presented a reduction of degradation between the years 1995/96 to 2006 (Bahia, Maranhão, Paraíba and Piauí) and, followed by a worsening in this scenario from 2006 to 2017, as well as in the total period from 1995/96 to 2017. Furthermore, the fact that the municipalities are inserted in the semiarid had a positive impact on their degradation.